The Trumpington Cross in context. (24th July 2017) - Lucy, Sam
Abstract: An Anglo-Saxon gold and garnet cloisonné pectoral cross from a seventh-century bed burial at Trumpington, Cambridgeshire is the fifth such example to be found. Details of the contextual associations of the five crosses are used to argue that these artifacts, and other high status cross-shaped pendants, were overt Christian symbols, strongly associated with high status female burials of the later seventh century. That one of the five examples was associated with the burial of St Cuthbert is highlighted as an anomaly, and could indicate that the Cuthbert Cross may have been a gift, rather than a personal possession of the saint.